(untitled) (Geo-Eco-Marina, 2020)
Corneliu Dinu, a bright figure of Romanian Geology, of Romanian science, left us after a life dedicated to Geology and to teaching of young specialists. A life in which Cornel, let me call him so, because we were bound by a warm friendship for many decades, which was based on the identical understanding of the basic notions of life, of human duty, of fairness and honesty and of professional interests, tried to give everything to society, to build and shape young people and specialists for the good of the country.